1990
DOI: 10.1007/bf01537219
|View full text |Cite
|
Sign up to set email alerts
|

Serum-ascites albumin gradients in nonalcoholic liver disease

Abstract: Several studies performed in alcoholics with advanced liver disease have demonstrated a positive correlation between the serum-ascites albumin gradient (SAAG) and measured portal venous pressure. A single study performed in 15 patients with exudative malignant ascites and 29 patients with alcoholic liver disease demonstrated that a SAAG of less than 1.1 was essentially diagnostic of a malignant origin of the ascites. In an effort to confirm and extend these observations to individuals with nonalcoholic liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
1
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
3
10
1
2
Order By: Relevance
“…The two groups showed statistically significant difference (P=0.001) based on presence and absence of varices. This is consistent with studies by Torres et al, Gurubacharya et al, Kajani et al, Dittrich et al [17][18][19][20] We also assessed the correlation between grade of varices and SAAG values. When the Value of SAAG was < 1.1 it was noted that Grade II and III varices were absent.…”
Section: Discussionsupporting
confidence: 89%
“…The two groups showed statistically significant difference (P=0.001) based on presence and absence of varices. This is consistent with studies by Torres et al, Gurubacharya et al, Kajani et al, Dittrich et al [17][18][19][20] We also assessed the correlation between grade of varices and SAAG values. When the Value of SAAG was < 1.1 it was noted that Grade II and III varices were absent.…”
Section: Discussionsupporting
confidence: 89%
“…9 The only study in the literature examining such a relationship, reported by Kajani and coworkers, in 24 patients with chronic nonalcoholic liver disease, showed no correlation (r=0.398) between measured portal venous pressure and SAAG, and three of their patients had a SAAG <1.1 g/dL. 10 We found five of our liver disease patients with a SAAG <1.1 g/dL. These were due to viral causes of liver cirrhosis and had no superimposed SBP or hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the lack of linear correlation between measured portal venous pressure and SAAG in nonalcoholic liver disease, 10 SAAG is still a useful diagnostic biochemical parameter, which can be used to separate ascites of liver disease (nonalcoholic) from other causes of ascites (malignancy and tuberculosis) and should replace the exudate/transudate concept in the differential diagnosis of ascites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il est également souligné dans la littérature qu'une relation directe existait entre le SAAG et les différentes mesures de l'HTP tels que le gradient de pression portale [14], la pression portale nette [15], ou la pression portale corrigée [16]. Selon Starling, le GASA peu invasif était un meilleur indicateur de l'HTP [9,17].…”
Section: Discussionunclassified